Does Instagram as Learning Media Affect Students’ Writing Skill on Recount Text?: An Experimental Research - Sallamah, Ismi Baqiatus; As Sabiq, Agus Husein (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2020)
This research's objectives were to examine whether Instagram as a Learning Media is useful toward students' writing recount text or not and measuring how significant the effect of Instagram on students’ writing recount text before and after treatment. This quasi-experimental research involved 35 students as participants from two different classes. Researchers took 10th graders from a selected private school in Purbalingga as research samples. Two IPS classes were selected, i.e., X IPS 1 was set as an experimental class, and X IPS 2 was set as a control class. The data were collected from the score of pre-test and post-test after the treatment. Researchers then compared the students’ achievement from control and experimental classes and analyzed the data using descriptive analysis and N-gain. The research findings indicated a significant achievement of students' competencies in using Instagram than conventional learning in writing recount text. The average N-gain score from experimental class and control class obtained 0.308 > 0.057. The Mean score of pre-test in experimental and control class obtained 69.875 > 64.818 and the Mean score of post-test in experimental and control class was 79.461 > 67.142. As a result, the experimental class's mean score was higher than the control class means Instagram as a Learning Media is useful in writing recount text.